Advances of Synergistic Electrocatalysis Between Single Atoms and Nanoparticles/Clusters - Luo, Guanyu; Song, Min; Zhang, Qian; An, Lulu; Shen, Tao; Wang, Shuang; Hu, Hanyu; Huang, Xiao; Wang, Deli (Nano-Micro Letters, 2024)
Combining single atoms with clusters or nanoparticles is an emerging tactic to design efficient electrocatalysts. Both synergy effect and high atomic utilization of active sites in the composite catalysts result in enhanced electrocatalytic performance, simultaneously provide a radical analysis of the interrelationship between structure and activity. In this review, the recent advances of single-atomic site catalysts coupled with clusters or nanoparticles are emphasized. Firstly, the synthetic strategies, characterization, dynamics and types of single atoms coupled with clusters/nanoparticles are introduced, and then the key factors controlling the structure of the composite catalysts are discussed. Next, several clean energy catalytic reactions performed over the synergistic composite catalysts are illustrated. Eventually, the encountering challenges and recommendations for the future advancement of synergistic structure in energy-transformation electrocatalysis are outlined. Highlights: 1 Fundamental principles for designing synergistic composite catalysts are reviewed. 2 The synergistic effect between various active sites, promoting electrocatalytic performance in different reactions are highlighted. 3 The challenges and perspectives for multiple active sites catalysts are discussed.